Mathematical model of multicriteria optimization for project of reengineering large-scale monitoring systems - Bezkorovainyi, V. V.; Podoliaka, K. E. (ХНУРЭ, 2015)
The analysis of modern projects and publications devoted to the design of largescale monitoring systems provided an opportunity to identify a set of indicators which impact the structural and topological characteristics of this class of systems. It has been proposed objectives for optimization, which take into account cost, reliability, operativeness, survivability and can improve the efficiency of the results of the solution of practical problems of reengineering.
Keywords: multicriteria optimization; reengineering large-scale monitoring system